Tradisi Bakar Batu pada Masyarakat Provinsi Papua Pegunungan Kabupaten Yahukimo dalam Perspektif Kebijakan Publik - Kabunggul, Orce (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2025)
Local traditions are often not an integral part of public policy, including in Yahukimo Regency, Highland Papua. One important tradition still practiced by the Mek Tribe is Bakar Batu, a cultural practice with social, economic, and ecological value. This study aims to analyze the role of the Bakar Batu tradition from a public policy perspective and its potential as a supporting element for sustainable development. The method used was descriptive qualitative with participatory observation, in-depth interviews, and document study. Data were obtained from traditional leaders, the community, and government officials, then analyzed using a successive approximation approach. The findings indicate that Bakar Batu plays a role in cultural preservation, conflict resolution, strengthening social cohesion, natural resource management, and improving the local economy. However, government policy support is still limited, particularly in aspects of funding, integration of cultural values in education, and legal protection of customary land. This tradition also has great potential in supporting environmental conservation and the development of cultural tourism based on the creative economy. Therefore, responsive, inclusive, and collaborative public policies are needed between the government, indigenous communities, and stakeholders so that the Bakar Batu tradition can contribute significantly to sustainable development in Highland Papua.